Composite semipermeable membrane
The composite semipermeable membrane with a structured separation functional layer enhances water permeability by incorporating protrusions with specific dimensions and densities, addressing the low-pressure operation challenge.
Patent Information
- Application Number
- JP2022175060
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-22
- Filing Date
- 2022-10-31
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-04-22
AI Technical Summary
Conventional composite semipermeable membranes exhibit inadequate water permeability during low-pressure operation.
A composite semipermeable membrane design featuring a support membrane with a separation functional layer containing protrusions formed of a thin film, where the protrusions have specific dimensions and densities, including a ratio of maximum width to base width greater than 1.3, and a thickness of 15 nm or more, with an average number density of 10 to 20 pieces/μm, enhancing water permeability.
The membrane achieves excellent water permeability even under low-pressure conditions, improving efficiency and performance.
Smart Images

Figure 0007616190000004 
Figure 0007616190000005 
Figure 0007616190000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite semipermeable membrane useful for selectively separating a liquid mixture. The composite semipermeable membrane obtained by the present invention can be suitably used, for example, for desalinizing seawater or brackish water. [Background technology]
[0002] Regarding the separation of mixtures, there are various technologies for removing substances (e.g., salts) dissolved in a solvent (e.g., water), but in recent years, the use of membrane separation methods has expanded as a process for saving energy and resources. Membranes used in membrane separation methods include microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, and reverse osmosis membranes, and these membranes are used, for example, to obtain drinking water from seawater, brackish water, and water containing harmful substances, to produce ultrapure water for industrial use, to treat wastewater, and to recover valuable materials.
[0003] In particular, composite semipermeable membranes having a crosslinked polyamide as a separation active layer have been proposed as reverse osmosis membranes and nanofiltration membranes. Methods for producing composite semipermeable membranes having a crosslinked polyamide as a separation active layer include a method of polymerization in the presence of an organic additive (Patent Documents 1 and 2), a method of polymerization in the presence of a monofunctional acid halide (Patent Document 3), and a method of polymerization in the presence of a partially hydrolyzed acid halide (Patent Document 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 08-224452 [Patent Document 2] Japanese Patent Application Publication No. 6-47260 [Patent Document 3] Japan Special Publication No. 2014-521499 [Patent Document 4] International Publication No. 2010 / 120326 Summary of the Invention [Problem to be solved by the invention]
[0005] Despite the various proposals described above, conventional composite semipermeable membranes have room for improvement in terms of water permeability during low-pressure operation. An object of the present invention is to provide a composite semipermeable membrane that exhibits excellent water generating properties even during low-pressure operation. [Means for solving the problem]
[0006] In order to achieve the above object, the present invention has the following configuration. [1] A composite semipermeable membrane comprising a support membrane and a separation functional layer provided on the support membrane, The separation functional layer has a plurality of protrusions formed of a thin film, A composite semipermeable membrane in which at least a portion of the multiple protrusions have a ratio Wa / Wb of the maximum width Wa to the base width Wb of the protrusion greater than 1.3 in any 10 cross sections having a length of 2.0 μm in the membrane surface direction of the support membrane. [2] The separation functional layer has a protrusion having a maximum diameter R of 30 nm or more of a circle contained therein. [1] Composite semipermeable membrane. [3] The average number density of the protrusions in the separation functional layer is 10 / μm or more and 20 / μm or less. The composite semipermeable membrane according to [1] or [2]. [4] The actual length L of the thin film per 1 μm length of the support film in the film surface direction of the thin film is 3.0 μm or more; The thickness of the thin film is 15 nm or more. [3] The composite semipermeable membrane according to the present invention. [5] In the plurality of protrusions, the ratio of the number of protrusions having a height of 200 nm or more to the number of protrusions having a height of 10 nm or more is 1 / 20 or more and 1 / 2 or less. [4] The composite semipermeable membrane according to the present invention. [6] In the plurality of protrusions, the ratio of the number of protrusions having a height of 400 nm or more to the number of protrusions having a height of 10 nm or more is 1 / 20 or more and 1 / 5 or less. [4] or [5]. The composite semipermeable membrane according to claim 1. Effect of the Invention
[0007] According to the present invention, a composite semipermeable membrane having excellent water generating ability can be obtained even during low pressure operation. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a cross-sectional view of a composite semipermeable membrane according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing the pleated structure of the thin film in the separation functional layer. [Diagram 3] FIG. 3 is a cross-sectional view of the pleated structure, and is a schematic diagram showing the height of the projections. [Figure 4] FIG. 4 is an enlarged cross-sectional view of a protrusion in a pleated structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these in any way. In this specification, "weight" and "mass", and "wt %" and "mass %" are treated as synonyms. A numerical range expressed using "~" means that the range includes the numerical values before and after "~" as the lower and upper limits.
[0010] 1.Composite semipermeable membrane The composite semipermeable membrane according to this embodiment includes a support membrane and a separation functional layer provided on the support membrane. (1-1) Support membrane In this embodiment, the support membrane does not substantially have a separation function for ions, etc., and provides strength to the separation functional layer that substantially has a separation function. The size and distribution of the pores of the support membrane are not particularly limited, but for example, a support membrane having uniform and fine pores, or pores that gradually become larger from the surface on which the separation functional layer is formed to the other surface, and the size of the pores on the surface on which the separation functional layer is formed is 0.1 nm to 100 nm, is preferable.
[0011] The material used for the support membrane and its shape are not particularly limited. For example, the support membrane may be a composite membrane having a substrate 2 and a porous support layer 3 provided on the substrate 2, as shown in FIG. 1, or it may be a membrane consisting of only one layer.
[0012] The substrate may be, for example, a fabric containing at least one material selected from polyester and aromatic polyamide as a main component. As the fabric, a long fiber nonwoven fabric or a short fiber nonwoven fabric can be preferably used.
[0013] The thickness of the substrate is preferably in the range of 10 μm or more and 200 μm or less, and more preferably in the range of 30 μm or more and 120 μm or less.
[0014] The porous support layer may contain at least one polymer selected from the group consisting of, for example, polysulfone; polyethersulfone; polyamide; polyester; cellulosic polymers such as cellulose acetate and cellulose nitrate; vinyl polymers such as polyethylene, polypropylene, polyvinyl chloride and polyacrylonitrile; homopolymers such as polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfone and polyphenylene oxide, and copolymers thereof.
[0015] Among them, polysulfone, cellulose acetate, polyvinyl chloride, or a mixture thereof is preferably used for the porous support layer, and it is particularly preferable to use polysulfone which has high chemical, mechanical and thermal stability.
[0016] The thickness of the porous support layer is preferably in the range of 10 to 200 μm, more preferably in the range of 20 to 100 μm. When the thickness of the porous support layer is 10 μm or more, good pressure resistance can be obtained and a uniform support membrane without defects can be obtained, and a composite semipermeable membrane including such a porous support layer can exhibit good salt removal performance. When the thickness of the porous support layer is 200 μm or less, the amount of unreacted substances remaining during production does not increase, and a decrease in chemical resistance due to a decrease in the amount of permeated water can be prevented.
[0017] In order for the composite semipermeable membrane to have sufficient mechanical strength and packing density, the thickness of the support membrane is preferably in the range of 30 to 300 μm, and more preferably in the range of 50 to 250 μm.
[0018] The morphology of the support membrane can be observed by a scanning electron microscope, a transmission electron microscope, an atomic force microscope, etc. For example, when observing the morphology of the support membrane by a scanning electron microscope, the porous support layer is peeled off from the substrate, and then cut by freeze fracturing to obtain a sample for cross-sectional observation. This sample is thinly coated with preferably platinum, platinum-palladium, or ruthenium tetrachloride, more preferably ruthenium tetrachloride, and observed by a high-resolution field emission scanning electron microscope (UHR-FE-SEM) at an accelerating voltage of 3 to 6 kV.
[0019] The thickness of the substrate, the porous support layer, and the composite semipermeable membrane can be measured by a digital thickness gauge. In addition, since the thickness of the separation functional layer described later is very thin compared to the support membrane, the thickness of the composite semipermeable membrane can also be considered as the thickness of the support membrane. Therefore, the thickness of the composite semipermeable membrane can be measured by a digital thickness gauge, and the thickness of the porous support layer can be calculated simply by subtracting the thickness of the substrate from the thickness of the composite semipermeable membrane. When using a digital thickness gauge, it is preferable to measure the thickness at 20 points and calculate the average value.
[0020] The thickness of the substrate, the porous support layer, and the composite semipermeable membrane may be measured by the above-mentioned microscope. The thickness is measured from an electron microscope photograph of a cross section observed at any five points for one sample, and the thickness is obtained by calculating the average value. Note that the thickness and pore size in this embodiment refer to the average value.
[0021] (1-2) Separation functional layer In the composite semipermeable membrane, it is the separation functional layer that has the substantial ability to separate ions, etc. In the cross-sectional view of the composite semipermeable membrane 1 in Fig. 1, the separation functional layer is indicated by the reference numeral "4". The separation functional layer has a plurality of protrusions formed of a thin film 11, as shown in Fig. 2.
[0022] The separation functional layer preferably contains polyamide as a main component. In the case of a separation functional layer mainly containing polyamide, the polyamide can be formed, for example, by interfacial polycondensation of a polyfunctional amine and a polyfunctional acid halide. Here, it is preferable that at least one of the polyfunctional amine and the polyfunctional acid halide contains a compound having three or more functional groups.
[0023] The thickness of the separating functional layer is usually within the range of 0.01 to 1 μm, and preferably within the range of 0.1 to 0.5 μm, in order to obtain sufficient separation performance and permeate amount.
[0024] Here, the polyfunctional amine refers to an amine having at least two primary amino groups and / or secondary amino groups in one molecule, at least one of which is a primary amino group. Examples of the polyfunctional amine include aromatic polyfunctional amines such as phenylenediamine, xylylenediamine, 1,3,5-triaminobenzene, 1,2,4-triaminobenzene, 3,5-diaminobenzoic acid, 3-aminobenzylamine, and 4-aminobenzylamine, in which two amino groups are bonded to a benzene ring at the ortho, meta, or para position, aliphatic amines such as ethylenediamine and propylenediamine, and alicyclic polyfunctional amines such as 1,2-diaminocyclohexane, 1,4-diaminocyclohexane, 4-aminopiperidine, and 4-aminoethylpiperazine.
[0025] Among them, in consideration of the selective separation property, permeability, and heat resistance of the membrane, aromatic polyfunctional amines having 2 to 4 primary amino groups and / or secondary amino groups in one molecule are preferable. As such polyfunctional aromatic amines, for example, m-phenylenediamine, p-phenylenediamine, 1,3,5-triaminobenzene, etc. are preferably used. Among them, m-phenylenediamine (hereinafter referred to as m-PDA) is more preferably used because of its easy availability and ease of handling.
[0026] These polyfunctional amines may be used alone or in combination of two or more. When using two or more simultaneously, the above amines may be combined with each other, or the above amine may be combined with an amine having at least two secondary amino groups in one molecule. Examples of the amine having at least two secondary amino groups in one molecule include piperazine and 1,3-bispiperidylpropane.
[0027] The polyfunctional acid halide refers to an acid halide having at least two halogenated carbonyl groups in one molecule. The trifunctional acid halide can be, for example, trimesic acid chloride, 1,3,5-cyclohexane tricarboxylic acid trichloride, 1,2,4-cyclobutane tricarboxylic acid trichloride, etc., and the bifunctional acid halide can be, for example, aromatic bifunctional acid halide such as biphenyl dicarboxylic acid dichloride, azobenzene dicarboxylic acid dichloride, terephthalic acid chloride, isophthalic acid chloride, naphthalenedicarboxylic acid chloride, etc., aliphatic bifunctional acid halide such as adipoyl chloride, sebacoyl chloride, etc., cyclopentane dicarboxylic acid dichloride, cyclohexane dicarboxylic acid dichloride, tetrahydrofuran dicarboxylic acid dichloride, etc., alicyclic bifunctional acid halide can be, for example,
[0028] Considering the reactivity with polyfunctional amine, the polyfunctional acid halide is preferably a polyfunctional acid chloride, and considering the selective separation property and heat resistance of the membrane, it is more preferable to use a polyfunctional aromatic acid chloride having 2 to 4 carbonyl chloride groups in one molecule. Among them, it is more preferable to use trimesoyl chloride as the polyfunctional acid halide from the viewpoint of easy availability and ease of handling. These polyfunctional acid halides may be used alone or in combination of two or more kinds.
[0029] In addition, in the separation functional layer, the thin film forms a pleated structure having multiple recesses and protrusions, as shown in Figure 2. Hereinafter, "protrusion" and "recess" refer to relatively protruding and recessed parts in the thin film, and in particular, the part above (away from the support film) the reference line A described below is called the protrusion, and the part below (towards the support film) is called the recess. A "protrusion" refers to the area from the bottom of a recess to the bottom of the adjacent recess, that is, one protrusion and the bottoms of the recesses on both sides of it. In addition, in this specification, a protrusion refers to a protrusion having a height equal to or greater than one-fifth of the 10-point average surface roughness of the thin film.
[0030] In the present embodiment, the separation functional layer preferably has an actual thin film length L of 3.0 μm or more per 1 μm of the support membrane in the membrane surface direction of the support membrane. When the actual thin film length L is 3.0 μm or more, the composite semipermeable membrane can obtain high water permeability. The actual thin film length L is more preferably 3.0 to 100 μm, and even more preferably 3.0 to 10 μm. In this specification, the term "film surface direction" refers to a direction perpendicular to the film surface.
[0031] The actual length L of the thin film can be determined according to a general method for determining a surface area or a specific surface area. The method is not particularly limited, but examples thereof include a method using an electron microscope such as a scanning electron microscope (SEM, FE-SEM) or a transmission electron microscope (TEM).
[0032] The method for measuring the actual length L of a thin film using a transmission electron microscope (TEM) is described below. First, to prepare ultrathin sections for the TEM, the sample is embedded in a water-soluble polymer. Any water-soluble polymer can be used as long as it can maintain the shape of the sample, such as PVA.
[0033] Next, to facilitate cross-sectional observation, the sample is stained with OsO4, and cut with an ultramicrotome to prepare ultrathin sections. The obtained ultrathin sections are photographed using an electron microscope. The observation magnification may be appropriately determined depending on the film thickness of the separation functional layer, but in order to observe the cross-sectional shape of the separation functional layer and to prevent the measurement from being localized, if the thickness of the separation functional layer is about 10 to 100 nm, the observation magnification may be set to 50,000 to 100,000 times.
[0034] For the cross-sectional photograph obtained above, the actual length of the thin film per 1 μm length of the support membrane in the membrane surface direction is measured at 10 random cross sections with a length of 2.0 μm, and the arithmetic mean value is calculated as the actual length L of the thin film in the composite semipermeable membrane.
[0035] The ten-point average surface roughness of a thin film can be obtained by the following method. A cross section perpendicular to the film surface is observed using an electron microscope. The observation magnification is preferably 10,000 to 100,000 times. In the obtained cross-sectional image, the surface of the thin film (indicated by the reference symbol "11" in FIG. 2) appears as a curve, as shown in FIG. 2. A roughness curve defined based on ISO4287:1997 is obtained for this curve. The average line of the roughness curve is obtained, also based on ISO4287:1997. The average line is a straight line drawn so that the total area of the region enclosed by the average line and the roughness curve is equal above and below the average line.
[0036] In the cross-sectional image with a length of 2.0 μm in the direction of the average line obtained above, the average line is set as the reference line A, and for the five convex parts from the highest convex part to the fifth highest, the heights from the reference line (the distance from the reference line to the apex of the convex part) H1 to H5 are measured and the average value is calculated. In addition, for the five concave parts from the deepest concave part to the fifth deepest, the depths (the distance from the reference line to the apex of the concave part) D1 to D5 are measured and the average value is calculated. The sum of the two average values obtained is the 10-point average surface roughness. The apex is the point on the convex part or concave part that is the greatest distance from the reference line.
[0037] The height of a protrusion is calculated as follows: For a protrusion that is at least one-fifth of the above-mentioned 10-point average surface roughness in a cross section 2.0 μm long in the direction of the above-mentioned average line, the sum of the average d of the depths d1 and d2 of the recesses at both ends of the protrusion (the distance from the reference line to the apex of the recess) and the height h of the protrusion (the distance from the reference line to the apex of the protrusion) is calculated as the protrusion height Ph.
[0038] In this embodiment, in any 10 cross sections having a length of 2.0 μm in the direction of the mean line, the ratio (N / M) of the number N of protrusions having a height of 200 nm or more present on the 10 cross sections to the number M of protrusions having a height of 10 nm or more present on the 10 cross sections is preferably 1 / 20 or more and 1 / 2 or less. When N / M is 1 / 20 or more, a composite semipermeable membrane with high water permeability can be obtained. N / M is more preferably 1 / 10 or more. Furthermore, when N / M is 1 / 2 or less, high water permeability can be obtained. N / M is more preferably 1 / 3 or less.
[0039] The number of protrusions present in 10 cross sections means the total sum of the number of protrusions found in each cross section for all 10 cross sections.
[0040] In this embodiment, it is preferable that in any 10 cross sections having a length of 2.0 μm in the direction of the mean line, all of the protrusions present in the 10 cross sections have at least one protrusion with a height of 400 nm or more. It is more preferable that the ratio (N1 / M) of the number N1 of protrusions with a height of 400 nm or more present in the 10 cross sections to the number M of protrusions with a height of 10 nm or more present in the 10 cross sections is 1 / 20 or more and 1 / 5 or less. By having protrusions with a height of 400 nm or more in the above range, a composite semipermeable membrane with high water permeability can be obtained.
[0041] As a result of intensive research by the present inventors, it was found that a composite semipermeable membrane exhibiting high water permeability can be obtained even during low-pressure operation when at least a portion of the multiple protrusions of the separation functional layer have a ratio (Wa / Wb) of the maximum width Wa of the protrusion to the base width Wb of the protrusion of greater than 1.3 in any 10 cross sections having a length of 2.0 μm in the membrane surface direction of the support membrane, as shown in FIG. 4. Wa / Wb is preferably 1.4 or more, more preferably 1.6 or more. In addition, in order to be compatible with the average number density of the protrusions, Wa / Wb is preferably 2.0 or less, more preferably 1.8 or less, and even more preferably 1.7 or less.
[0042] The maximum width Wa of the protrusions and the width Wb of the base of the protrusions can be observed by a scanning electron microscope or a transmission electron microscope. For example, when observing the maximum width Wa of the protrusions and the width Wb of the base of the protrusions by a scanning electron microscope, a composite semipermeable membrane sample is thinly coated with preferably platinum, platinum-palladium, or ruthenium tetroxide, more preferably ruthenium tetroxide, and observed by using a high-resolution field emission scanning electron microscope (UHR-FE-SEM) at an accelerating voltage of 3 to 6 kV.
[0043] As the high-resolution field emission scanning electron microscope, a Hitachi S-900 type electron microscope or the like can be used. The observation magnification is preferably 5,000 to 100,000 times. Taking into consideration the observation magnification, the maximum width Wa of the protrusion and the base width Wb of the protrusion can be directly measured using a scale or the like from the obtained electron microscope photograph. Note that both the maximum width Wa of the protrusion and the base width Wb of the protrusion are measured as the distance between the inner surfaces of the protrusions. In addition, the base width Wb of the protrusion is the distance between the straight lines drawn from the apexes of the recesses on both sides of the protrusion perpendicular to the reference line.
[0044] In any 10 cross sections of 2.0 μm in the membrane surface direction of the support membrane, the ratio of the number of protrusions present in the 10 cross sections with Wa / Wb greater than 1.3 to the total number of protrusions present in the 10 cross sections is preferably 20% or more. By making this ratio 20% or more, the water permeability of the composite semipermeable membrane can be improved. The ratio is more preferably 40% or more, and even more preferably 50% or more.
[0045] In addition, the separation functional layer in this embodiment preferably has protrusions with a maximum diameter of a circle contained inside the protrusion, i.e., a packed circle diameter R of 30 nm or more. By having protrusions with a packed circle diameter R of 25 nm or more, the water permeability of the composite semipermeable membrane is improved. It is more preferable that the composite semipermeable membrane includes protrusions with a packed circle diameter R of more preferably 32 nm or more, and even more preferably 35 nm or more. In order to suppress a decrease in the average number density of the protrusions, it is preferable that the packed circle diameter R is 80 nm or less. The packed circle diameter R can be measured from a cross-sectional photograph of the separation functional layer.
[0046] In any 10 cross sections having a length of 2.0 μm in the film surface direction, the proportion of the number of protrusions having a packed circle diameter R of 25 nm or more present in the 10 cross sections to the total number of protrusions present in the 10 cross sections is preferably 20% or more, more preferably 40% or more, and even more preferably 50% or more.
[0047] In the separation functional layer of this embodiment, the average number density of the protrusions is preferably 10 / μm or more, more preferably 12 / μm or more. The average number density of the protrusions in the separation functional layer is preferably 20 / μm or less.
[0048] When the average number density of the projections is 10 / μm or more, the composite semipermeable membrane has sufficient water permeability, and deformation of the projections when pressurized can be suppressed, resulting in stable membrane performance. When the average number density of the projections is 20 / μm or less, the growth of the pleated structure occurs sufficiently, and a composite semipermeable membrane with the desired water permeability can be easily obtained.
[0049] The average number density of protrusions can be measured by observing 10 cross sections of a length of 2.0 μm in the film surface direction described above, and counting the number of protrusions that are at least one-fifth of the 10-point average surface roughness described above in each cross section.
[0050] 2. Manufacturing method An example of a method for producing the composite semipermeable membrane of the present embodiment described above will be described below. (2-1) Formation of separation functional layer The process of forming a separation functional layer on a support membrane will be described. In the following, an example will be given in which the support membrane has a substrate and a porous support layer. When the support membrane does not include a substrate, the "porous support layer surface" and "on the porous support layer" can be read as the "support membrane surface" and "on the support membrane", respectively.
[0051] The process of forming the separation functional layer includes a step of contacting a polyfunctional amine solution with a polyfunctional acid halide solution on the porous support layer to form a polyamide by an interfacial polycondensation reaction. More specifically, the step of forming the separation functional layer includes: (i) contacting a porous support layer with a multifunctional amine solution; (ii) after the step (i), a step of producing a polyamide on the porous support layer by interfacial polycondensation by contacting the porous support layer with a polyfunctional acid halide solution. Each production step will be described in detail below.
[0052] The polyfunctional amine solution is an aqueous solution, and the polyfunctional amine concentration in this solution is preferably within the range of 0.1 to 20% by weight, more preferably within the range of 0.5 to 15% by weight. When the polyfunctional amine concentration is within the above range, a composite semipermeable membrane having sufficient salt removal performance and water permeability can be obtained.
[0053] The aqueous polyfunctional amine solution may contain a surfactant, an organic solvent, an alkaline compound, an antioxidant, and the like, so long as they do not interfere with the reaction between the polyfunctional amine and the polyfunctional acid halide.
[0054] Examples of the surfactant include compounds having a polyoxyalkylene structure, a fatty acid ester structure, or a hydroxyl group. Examples of the polyoxyalkylene structure include -(CH2CH2O) n -, -(CH2CH2(CH3)O) n -, -(CH2CH2CH2O) n -, -(CH2CH2CH2CH2O) n - and the like. Examples of the fatty acid ester structure include fatty acids having a long-chain aliphatic group. The long-chain aliphatic group may be either linear or branched, and examples of the fatty acid include stearic acid, oleic acid, lauric acid, palmitic acid, and salts thereof. Examples of fatty acid esters derived from fats and oils include beef tallow, palm oil, coconut oil, and the like. Examples of surfactants having a sulfo group include 1-hexanesulfonic acid, 1-octanesulfonic acid, 1-decanesulfonic acid, 1-dodecanesulfonic acid, perfluorobutanesulfonic acid, toluenesulfonic acid, cumenesulfonic acid, and octylbenzenesulfonic acid. Examples of surfactants having a hydroxyl group include ethylene glycol, propylene glycol, 2-propanediol, 1,4-butanediol, glycerin, sorbitol, glucose, and sucrose. The surfactant has the effect of improving the wettability of the porous support layer surface and reducing the interfacial tension between the amine aqueous solution and the nonpolar solvent.
[0055] Examples of the organic solvent include linear amide compounds and cyclic amide compounds. Examples of the linear amide compounds include N-methylformamide, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, and N,N-diethylacetamide. Examples of the cyclic amide compounds include N-methylpyrrolidinone, γ-butyrolactam, and ε-caprolactam. The organic solvent may act as a catalyst for the interfacial polycondensation reaction, and the addition of the organic solvent may allow the interfacial polycondensation reaction to be carried out efficiently.
[0056] Examples of alkaline compounds include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, inorganic carbonates and bicarbonates such as sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate, and organic compounds such as tetramethylammonium hydroxide and tetraethylammonium hydroxide.
[0057] Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, sulfur-based antioxidants, and phosphorus-based antioxidants. Examples of the phenol-based antioxidants (including hindered phenol-based antioxidants) include 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), and tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane. Examples of the amine-based antioxidants include phenyl-β-naphthylamine, α-naphthylamine, N,N'-di-sec-butyl-p-phenylenediamine, phenothiazine, and N,N'-diphenyl-p-phenylenediamine. Examples of sulfur-based antioxidants include dilauryl 3,3'-thiodipropionate, distearyl thiodipropionate, lauryl stearyl thiodipropionate, and dimyristyl 3,3'-thiodipropionate. Examples of phosphorus-based antioxidants include triphenyl phosphite, octadecyl phosphite, and trinonylphenyl phosphite. Examples of other antioxidants include ascorbic acid or an alkali metal salt thereof, sterically hindered phenolic compounds such as dibutylhydroxytoluene and butylhydroxyanisole, isopropyl citrate, dl-α-tocopherol, nordihydroguaiaretic acid, and propyl gallate.
[0058] The contact of the aqueous polyfunctional amine solution with the porous support layer is preferably carried out uniformly and continuously on the surface of the porous support layer.Specific examples of the method include a method of applying the aqueous polyfunctional amine solution to the porous support layer, or a method of immersing the porous support layer in the aqueous polyfunctional amine solution.The contact time between the porous support layer and the aqueous polyfunctional amine solution is preferably within a range of 1 to 10 minutes, and more preferably within a range of 1 to 3 minutes.
[0059] After the polyfunctional amine aqueous solution is brought into contact with the porous support layer, it is preferable to thoroughly drain the solution so that no droplets remain on the membrane. By thoroughly draining the solution, it is possible to prevent the remaining droplets from becoming membrane defects after membrane formation, which leads to a decrease in membrane performance. As a method for draining the solution, for example, as described in Japanese Patent Application Laid-Open No. 2-78428, a method in which the support membrane after contact with the polyfunctional amine aqueous solution is held vertically to allow excess aqueous solution to flow naturally, or a method in which an air current such as nitrogen is blown from an air nozzle to forcibly drain the solution can be used. In addition, after draining, the membrane surface can be dried to remove some of the water content of the aqueous solution.
[0060] Step (ii) will now be described. Step (ii) is a step of producing a polyamide on the porous support layer by contacting the porous support layer with a polyfunctional acid halide or an organic solvent solution containing a polyfunctional acid halide through interfacial polycondensation.
[0061] The concentration of the polyfunctional acid halide in the organic solvent solution is preferably in the range of 0.01 to 10% by weight, more preferably in the range of 0.02 to 2.0% by weight. A concentration of 0.01% by weight or more ensures a sufficient reaction rate, while a concentration of 10% by weight or less can suppress the occurrence of side reactions.
[0062] The organic solvent is preferably one that is immiscible with water, dissolves the polyfunctional acid halide, and does not destroy the support film, and is inactive against the polyfunctional amine compound and the polyfunctional acid halide. Preferred examples of the organic solvent include hydrocarbon compounds such as n-hexane, n-octane, n-nonane, n-decane, n-undecane, n-dodecane, isodecane, and isododecane.
[0063] The polyfunctional acid halide solution preferably contains water. When the polyfunctional acid halide solution contains water, the above-mentioned shape of the protrusions is realized. The amount of water contained in the polyfunctional acid halide solution is preferably 1 to 500 ppm, more preferably 1 to 200 ppm.
[0064] The polyfunctional acid halide solution may contain a compound represented by chemical formula (I) (hereinafter referred to as compound (I)).
[0065] [ka]
[0066] In the above formula, R1 and R2 are each independently an alkyl group having one or more carbon atoms.
[0067] Compound (I) is preferably an aromatic ester, and particularly preferably a phthalate ester.Specific examples of compound (I) include dibutyl phthalate, dibutylbenzyl phthalate, diethylhexyl phthalate, diisodecyl phthalate, diisonoyl phthalate, dioctyl phthalate, diisobutyl phthalate, diethyl phthalate, dimethyl phthalate, diisooctyl phthalate, dipropyl phthalate, dicyclohexyl phthalate, dinonyl phthalate, dipentyl phthalate, dihexyl phthalate, dibenzyl phthalate, diphenyl phthalate, and bis(2-ethylhexyl) phthalate.
[0068] The concentration of compound (I) in the polyfunctional acid halide solution can be changed depending on the type of compound (I) to be added, but is preferably within the range of 5 ppm to 500 ppm.
[0069] The method for contacting the organic solvent solution containing the polyfunctional acid halide with the aqueous solution phase of the polyfunctional amine compound includes coating or dropping.
[0070] In step (ii), a layer of a polyfunctional acid halide solution is formed on the layer of the polyfunctional amine aqueous solution on the porous support layer, and preferably a gradient is formed in the layer of the polyfunctional acid halide solution, with the water content increasing closer to the porous support layer.
[0071] The above gradient is formed immediately (within about 5 seconds) after the layer of the polyfunctional amine aqueous solution and the layer of the polyfunctional acid halide solution are brought into contact with each other, which generates a difference in surface tension inside the layer of the polyfunctional acid halide solution and generates a flow within the layer of the polyfunctional acid halide solution. This flow forms protrusions in the pleated structure of the separation functional layer that are thin at the base and bulging at the body, improving the water permeability of the composite semipermeable membrane.
[0072] The gradient can be formed, for example, by applying a multifunctional acid halide solution having a different water content multiple times onto the porous support layer. The number of applications is preferably two. The water content of the first applied multifunctional acid halide solution (first multifunctional acid halide solution) is preferably 10 to 500 ppm, more preferably 10 to 200 ppm. The water content of the second applied multifunctional acid halide solution (second multifunctional acid halide solution) is preferably 1 to 300 ppm, more preferably 1 to 150 ppm.
[0073] When forming a separation functional layer containing a crosslinked polyamide by interfacial polycondensation, the process is carried out in the presence of compound (I), whereby the actual length of the thin film of the separation functional layer can be increased and a separation functional layer with a large thin film thickness can be formed, resulting in a composite semipermeable membrane exhibiting high water permeability.
[0074] Although the mechanism of action of compound (I) is unclear, it is believed that the interaction between the aromatic rings present in compound (I) and the aromatic rings present in the polyamide in the process of being formed is influential. In detail, in the interfacial polycondensation of a polyfunctional amine and a polyfunctional acid halide, when the amine diffuses from the polyfunctional amine aqueous solution side to the organic solvent side containing the polyfunctional acid halide, the presence of compound (I) makes the concentration gradient of the amine gentle, and as a result, the formation time of the protrusions in the separation functional layer becomes sufficiently long, the formation of the protrusion structure is facilitated, and both the surface area of the protrusions and the thickness of the thin film are thought to be large.
[0075] At this time, by forming a flow within the layer of the polyfunctional acid halide solution, i.e., the layer of the organic solvent, the formation of protrusions is further promoted, and the height of the protrusions can be increased while obtaining a shape with a thin base and a bulging body.
[0076] By giving the protrusions of the separation functional layer a shape that is thin at the base, bulging at the body, and large in height, it is possible to reduce the area of contact with adjacent protrusions while maintaining the specific surface area, thereby ensuring the effective membrane area and resulting in higher water permeability.
[0077] The temperature of the membrane surface immediately after contacting the aqueous polyfunctional amine solution with the polyfunctional acid halide solution is preferably within the range of 25 to 60°C, more preferably within the range of 30 to 50°C. By setting the temperature of the membrane surface at 25°C or higher, the pleated structure grows larger, improving the permeation flux. In addition, by setting the temperature of the membrane surface at 60°C or lower, a composite semipermeable membrane exhibiting a good salt rejection rate can be obtained.
[0078] The method of applying temperature to the membrane surface may be to heat the support membrane or to contact the membrane with a heated organic solvent solution of the polyfunctional acid halide. The temperature of the membrane surface immediately after contacting the aqueous polyfunctional amine solution with the polyfunctional acid halide solution can be measured by a non-contact thermometer such as a radiation thermometer.
[0079] As described above, after the polyfunctional amine aqueous solution is brought into contact with the organic solvent solution of the polyfunctional acid halide to carry out interfacial polycondensation and the separation functional layer containing the crosslinked polyamide is formed on the porous support layer, the excess solvent may be drained off. For example, the method of draining off the liquid may be a method of holding the membrane vertically and removing the excess organic solvent by gravity. In this case, the time for holding vertically is preferably 1 to 5 minutes, more preferably 1 to 3 minutes. If this time is 1 minute or more, a sufficient amount of polyamide can be formed as the separation functional layer, and if it is 5 minutes or less, the organic solvent does not evaporate too much, and the occurrence of defects in the membrane can be suppressed.
[0080] (2-2) Formation of the support membrane The support film may be a commercially available filter. Alternatively, a support film having a substrate and a porous support layer may be formed by applying a polymer solution onto a substrate and then solidifying the polymer, or by applying a polymer solution onto a substrate such as glass, then solidifying the polymer, and peeling the polymer off from the substrate.
[0081] For example, when forming a support membrane using polysulfone, polysulfone is dissolved in N,N-dimethylformamide (hereinafter referred to as DMF) to obtain a polymer solution, which is applied to a substrate to a certain thickness and then wet-coagulated in water. This method makes it possible to obtain a porous support layer in which most of the surface has fine pores with diameters of several tens of nanometers or less.
[0082] (2-3) Other processing The composite semipermeable membrane after the separation functional layer is formed can have improved salt removal performance and water permeability by adding a process of hot water treatment at preferably 50 to 150°C, more preferably 70 to 130°C, preferably for 1 second to 10 minutes, more preferably 1 minute to 8 minutes.
[0083] In addition, the salt rejection rate can be further improved by including a step of contacting the composite semipermeable membrane with a compound (A) that reacts with a primary amino group on the separation functional layer after the hot water treatment to produce a diazonium salt or a derivative thereof, and then contacting it with a water-soluble compound (B) that is reactive with the compound (A).
[0084] Examples of the compound (A) that reacts with a primary amino group to generate a diazonium salt or a derivative thereof include aqueous solutions of nitrous acid and its salts, nitrosyl compounds, etc. Since aqueous solutions of nitrous acid and nitrosyl compounds generate gas and are easily decomposed, it is preferable to sequentially generate nitrous acid, for example, by reacting a nitrite with an acidic solution. In general, nitrite reacts with hydrogen ions to generate nitrous acid (HNO2), which can be efficiently generated when the pH of the aqueous solution is preferably 7 or less, more preferably 5 or less, and even more preferably 4 or less. Among these, an aqueous solution of sodium nitrite reacted with hydrochloric acid or sulfuric acid in an aqueous solution is particularly preferable from the viewpoint of ease of handling.
[0085] When sodium nitrite is used as the compound (A) that reacts with the primary amino group to generate a diazonium salt or a derivative thereof, the concentration of sodium nitrite is preferably in the range of 0.01 to 1% by weight. When the sodium nitrite is within the above range, the effect of generating a sufficient diazonium salt or a derivative thereof is obtained, and the solution is easy to handle.
[0086] The temperature of the compound is preferably 15° C. to 45° C. Within this range, the reaction does not take too long, and the decomposition of nitrous acid is not too rapid, making handling easy.
[0087] The contact time between the primary amino group and the compound may be long enough to generate a diazonium salt and / or its derivative, and if the concentration is high, the treatment can be completed in a short time, but if the concentration is low, a long time is required. Therefore, in the solution of the above concentration, the contact time is preferably within 10 minutes, and more preferably within 3 minutes.
[0088] The method of contacting the primary amino group with the compound is not particularly limited, and the compound may be applied (coated) in a solution, or the composite semipermeable membrane may be immersed in the compound solution. Any solvent may be used to dissolve the compound, as long as the compound dissolves and the composite semipermeable membrane is not eroded. The compound solution may contain a surfactant, an acidic compound, an alkaline compound, or the like, as long as it does not interfere with the reaction between the primary amino group and the reagent.
[0089] Next, the composite semipermeable membrane in which the diazonium salt or its derivative is produced is contacted with a water-soluble compound (B) that reacts with the diazonium salt or its derivative. Examples of the water-soluble compound (B) that reacts with the diazonium salt or its derivative include chloride ions, bromide ions, cyanide ions, iodide ions, fluoroboric acid, hypophosphorous acid, sodium hydrogen sulfite, sulfite ions, aromatic amines, phenols, hydrogen sulfide, and thiocyanic acid.
[0090] When reacted with sodium hydrogen sulfite or sulfite ions, a substitution reaction occurs instantly, and amino groups are replaced with sulfo groups. In addition, when it is brought into contact with aromatic amines or phenols, a diazo coupling reaction occurs, making it possible to introduce aromatic groups onto the membrane surface.
[0091] These compounds may be used alone or in combination, or may be contacted with different compounds multiple times. The compounds to be contacted with the composite semipermeable membrane in which the diazonium salt or its derivative is formed are preferably sodium hydrogen sulfite and sulfite ion.
[0092] The concentration and time for contacting the composite semipermeable membrane in which the diazonium salt or its derivative is formed with the water-soluble compound (B) which reacts with the diazonium salt or its derivative can be appropriately adjusted in order to obtain the desired effect.
[0093] The temperature at which the composite semipermeable membrane containing the diazonium salt or its derivative is contacted with the water-soluble compound (B) that reacts with the diazonium salt or its derivative is preferably 10 to 90° C. When the contact temperature is within the above range, the reaction proceeds easily, while a decrease in the amount of permeated water due to shrinkage of the polymer does not occur.
[0094] In addition, the membrane before and after the treatment in this section (2-3) is referred to as a "composite semipermeable membrane", and the layer on the support membrane in the membrane before and after the treatment in this section (2-3) is referred to as a "separation functional layer".
[0095] (3) Use of composite separation membranes The composite semipermeable membrane of the present embodiment thus produced is wound around a cylindrical water collection pipe having a large number of holes, together with a raw water flow path material such as a plastic net, a permeate water flow path material such as tricot, and, if necessary, a film for increasing pressure resistance, and is suitably used as a spiral-type composite semipermeable membrane element. Furthermore, this element can also be connected in series or in parallel and housed in a pressure vessel to form a composite semipermeable membrane module.
[0096] Furthermore, the above-mentioned composite semipermeable membrane and its elements and modules can be combined with a pump that supplies raw water to them, a device that pretreats the raw water, etc. to form a fluid separation device. By using this separation device, raw water can be separated into permeated water such as drinking water and concentrated water that did not permeate the composite semipermeable membrane, thereby obtaining water suitable for the purpose.
[0097] The salt removal rate improves as the operating pressure of the fluid separation device increases; however, the energy required for operation also increases. Taking into consideration the durability of the composite semipermeable membrane, the operating pressure when passing the treated water through the composite semipermeable membrane is preferably 0.5 MPa or more and 10 MPa or less.
[0098] As the feed water temperature increases, the salt rejection rate of the composite semipermeable membrane decreases, but as the temperature decreases, the membrane permeation flux also decreases, so it is preferable that the temperature be 5° C. or higher and 45° C. or lower. Furthermore, as the pH of the feed water increases, in the case of high-salt feed water such as seawater, there is a risk of magnesium scale formation, and there is also concern that high-pH operation may cause deterioration of the composite semipermeable membrane, so operation in the neutral region is preferable.
[0099] Examples of raw water to be treated by the composite semipermeable membrane according to the present embodiment include liquid mixtures containing 50 mg / L to 100 g / L of salt (total dissolved solids), such as seawater, brackish water, and wastewater. In general, salt refers to the total dissolved solids content, and is expressed as "mass / volume" or "weight ratio." According to the definition, it can be calculated from the weight of the residue obtained by evaporating a solution filtered through a 0.45 μm filter at a temperature of 39.5 to 40.5° C., but it is more convenient to convert it from the practical salinity (S). EXAMPLES
[0100] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0101] (Reference example 1) A support membrane was prepared by casting an 18 wt % solution of polysulfone in DMF onto a polyester nonwoven fabric made of long fibers at room temperature (25°C) to a thickness of 200 μm, and then immediately immersing the fabric in pure water for 5 minutes.
[0102] Example 1 The support membrane obtained in Reference Example 1 was immersed in an aqueous solution containing 4% by weight of m-phenylenediamine (m-PDA) for 2 minutes, the support membrane was slowly pulled up vertically, and excess aqueous solution was removed from the support membrane surface by blowing nitrogen from an air nozzle. Next, a n-decane solution (water content 23 ppm) containing 0.12% by weight of trimesoyl chloride (TMC) was applied as a first polyfunctional acid halide solution so that the support membrane surface was completely wet.
[0103] Within 5 seconds, a second polyfunctional acid halide solution, a n-decane solution (water content 10 ppm) containing 0.12 wt% trimesoyl chloride (TMC), was applied on top of the layer of the first polyfunctional acid halide solution so that the surface of the support membrane was completely wetted. The membrane was then heated in an oven at 100°C, and then the membrane was vertically drained to remove excess solution from the membrane, and dried by blowing air at 20°C onto it using a blower. Finally, the membrane was washed with pure water at 90°C to obtain a composite semipermeable membrane.
[0104] The amounts of water contained in the first and second multifunctional acid halide solutions are shown in Table 1. Table 2 shows the maximum width Wa of the protrusions on the surface of the separating functional layer, the base width Wb of the protrusions, the maximum width Wa of the protrusions / the base width Wb of the protrusions, the average number density of the protrusions, the packed circle diameter, the actual length of the thin film, the height of the protrusions (presence ratio), the thickness of the thin film, and the membrane permeation flux of the obtained composite semipermeable membrane.
[0105] (Examples 2 to 11) A composite semipermeable membrane was obtained in the same manner as in Example 1, except that the water content in the first and second polyfunctional acid halide solutions was changed to the concentrations shown in Table 1.
[0106] (Examples 12 to 17) A composite semipermeable membrane was obtained in the same manner as in Example 1, except that the amount of water contained in the first and second multifunctional acid halide solutions was changed to the concentrations shown in Table 1, and additives were added to the first and second multifunctional acid halide solutions. The types and concentrations of the additives contained in the first and second multifunctional acid halide solutions are as shown in Table 1.
[0107] (Comparative Examples 1 to 2) A composite semipermeable membrane was obtained in the same manner as in Example 1, except that only the first polyfunctional acid halide solution containing the water amount shown in Table 1 was applied.
[0108] (Comparative Examples 3 to 4) A composite semipermeable membrane was obtained in the same manner as in Example 1, except that the water content in the first and second polyfunctional acid halide solutions was changed to the concentrations shown in Table 1.
[0109] Comparative Example 5 The support membrane obtained in Reference Example 1 was immersed in an aqueous solution containing 2.0 wt% m-PDA and 1.5 wt% N-methylpyrrolidone as an additive for 2 minutes, the support membrane was slowly pulled up vertically, and nitrogen was sprayed from an air nozzle to remove excess aqueous solution from the support membrane surface. Next, a hexane solution containing 0.05 wt% trimesoyl chloride and 1 wt% ethyl caprylate as an additive as the first and second polyfunctional acid halide solutions was applied in order so that the surface of the support membrane was completely wet. The water content of the first and second polyfunctional acid halide solutions is as shown in Table 1. After that, in order to remove excess solution from the membrane, the membrane was placed vertically to drain the liquid, and then dried by blowing air at 20°C using a blower. Finally, the membrane was washed with pure water at 90°C to obtain a composite semipermeable membrane.
[0110] Comparative Example 6 The support membrane obtained in Reference Example 1 was immersed in 2.0% by weight of m-PDA for 2 minutes, the support membrane was slowly pulled up vertically, and nitrogen was blown from an air nozzle to remove excess aqueous solution from the support membrane surface. Next, the aqueous solution was concentrated at 80°C for 1 minute using a hot air dryer, and then n-decane solutions containing 0.1% by weight of trimesoyl chloride were applied in order as the first and second polyfunctional acid halide solutions so that the surface of the support membrane was completely wet. The water content of the first and second polyfunctional acid halide solutions is as shown in Table 1. After that, in order to remove excess solution from the membrane, the membrane was placed vertically to drain the liquid, and then dried by blowing air at 20°C using a blower. Finally, the membrane was washed with pure water at 90°C to obtain a composite semipermeable membrane.
[0111] (Maximum width of protrusions in the separation functional layer, base width of protrusions, measurement of filling circle diameter, height of protrusions (proportion), thickness of thin film, actual length of thin film) These parameters were measured by the method described above. The coating of the sample was ruthenium tetroxide, and a Hitachi S-900 type high-resolution field emission scanning electron microscope was used.
[0112] (Method for measuring the average number density of protrusions on the separation functional layer) The composite semipermeable membrane sample was embedded in epoxy resin, stained with OsO4 to facilitate cross-sectional observation, and cut with an ultramicrotome to prepare 10 ultrathin sections. The obtained ultrathin sections were photographed using a transmission electron microscope. The accelerating voltage during observation was 100 kV, and the observation magnification was 10,000 times. For the obtained cross-sectional photograph, the number of protrusions in a cross section with a length of 2.0 μm in the membrane surface direction was measured using a scale, and the 10-point average surface roughness was calculated as described above. Based on this 10-point average surface roughness, the parts having a height of 1 / 5 or more of the 10-point average surface roughness were counted as protrusions, and the average number density of protrusions in the separation functional layer was calculated.
[0113] (Water content in polyfunctional acid halide solution) The amount of water contained in the polyfunctional acid halide solution was measured five times in advance using a trace water content measuring device CA-05 manufactured by Mitsubishi Chemical Industries, Ltd., and the average value was calculated.
[0114] (Membrane performance evaluation under low pressure) (membrane flux) The raw water (NaCl concentration 3.2%, boron concentration approximately 5 ppm) adjusted to a temperature of 25°C and pH 6.5 was supplied to the composite semipermeable membrane at an operating pressure of 4.1 MPa and membrane filtration was performed for 24 hours. The amount of water passing through the membrane was calculated as the membrane permeation flux (m 2 ) in terms of the amount of water passing through the membrane (cubic meters) per day per square meter of membrane surface. 3 / m 2 / day).
[0115] [Table 1]
[0116] [Table 2]
[0117] From the results in Table 2, Examples 1 to 17 had higher membrane permeation flux values in low pressure operation than the Comparative Example.
[0118] Although the present invention has been described in detail and with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2021-072382) filed on April 22, 2021, the contents of which are incorporated herein by reference. [Industrial Applicability]
[0119] The composite semipermeable membrane of the present invention can be suitably used, particularly, for desalinizing seawater or brackish water.
Claims
[Claim 1] A method for producing a composite semipermeable membrane having a substrate, a porous support layer, and a separation functional layer, comprising the steps of: forming the separation functional layer on the porous support layer, The step of forming the separation functional layer includes: (i) contacting the porous support layer with a m-phenylenediamine solution; (ii) after the step (i), contacting the porous support layer with an organic solvent solution containing trimesoyl chloride to produce a polyamide on the porous support layer by interfacial polycondensation; having The step (ii) includes first applying a first organic solvent solution containing trimesoyl chloride having a water content of 10 to 200 ppm to the porous support layer, and then applying a second organic solvent solution containing trimesoyl chloride having a water content of 1 to 150 ppm to the porous support layer, thereby forming a gradient containing a higher water content closer to the porous support layer; the water content of the first organic solvent solution containing trimesoyl chloride is 6 ppm or more higher than the water content of the second organic solvent solution containing trimesoyl chloride; A method for producing a composite semipermeable membrane.
Citation Information
Patent Citations
Preparation method for ultra-low-pressure high-flux reverse osmosis membrane
CN104607067A
Production of thin composite film
JP1994047260A
Productionn of high permeable composite reverse osmosis membrane
JP1996224452A
Composite semipermeable membrane, method for producing the same, and element, fluid separation device, and water treatment method using the same
JP2008517737A
Polyamide-based reverse osmosis separation membrane with excellent initial permeate flow rate and method for producing the same
JP2014521499A